Inundation characteristics of mangrove and saltmarsh in micro-tidal estuaries. (31st October 2021) - Kumbier, Kristian; Hughes, Michael G.; Rogers, Kerrylee; Woodroffe, Colin D.
Abstract: Tidal inundation is a principal driver in intertidal wetland functioning. A combination of surface elevation and its relation to tidal range creates inundation regimes that influence a range of abiotic factors that affect wetland species distribution. Hydroperiod is a term frequently used to describe inundation regimes; however, the term has been vaguely defined in the past and typically quantified using tide gauge data rather than empirical field observations. This study explores relationships between various characteristics, such as frequency, total duration, average duration, average depth, non-tidal exposure, and mangrove/saltmarsh distribution in micro-tidal estuarine settings of southeast Australia. Inundation was measured directly using 35 pressure transducers embedded into mangrove and saltmarsh substrates over a period of two lunar tidal cycles along six transects located at Clyde and Minnamurra River estuaries, New South Wales, Australia. Results indicated differences in wetland inundation characteristics between mangrove and saltmarsh that are a function of wetland microtopography and site-specific tidal regime (e.g. local tidal range). For example, mangroves were inundated approximately 15–70% of the time, and 0.9–2 times a day, whereas saltmarshes were submerged only <15% of the time and less than 0.9 times per day. Comparison of direct field measurements and tide gauge-derived estimates of wetland inundation regime revealed that nearby gauge data may provide an acceptable estimate; however, distant tide gauge data provided poor estimates due to the effect of tidal dampening and amplification, respectively. Detailed analysis of wetland inundation characteristics as presented in this study demonstrates a method for describing inundation regimes at local scale. Improved understanding of contemporary tidal inundation dynamics in mangrove and saltmarsh can support modelling of wetland response to sea-level rise, as well as restoration practises by providing estimates of inundation tolerances. Highlights: Wetland inundation regime combines tidal frequency, depth and non-tidal exposure The term hydroperiod may be used for temporal characteristics only (e.g. duration) Boundaries in wetland inundation regime separate mudflat, mangrove and saltmarsh Nearby tide gauges provided reasonable estimates of wetland inundation regime Distant tide gauges may over- and underestimate wetland inundation regime